2015
DOI: 10.1074/jbc.m115.667022
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Nbp35-Cfd1 Cytosolic Iron-Sulfur Cluster Scaffold Is an ATPase

Abstract: Background: Nbp35 and Cfd1 are iron-sulfur cluster scaffolds with an NTPase domain of unknown function. Results: Nucleotide binding and hydrolysis assays paired with mutagenesis demonstrate ATP hydrolysis by these cluster scaffolds. Conclusion: Nbp35 and the Nbp35-Cfd1 complex are ATPases. Significance: This first demonstration of ATPase activity enables future investigation of how nucleotide influences cluster biogenesis by this large family of proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 30 publications
9
66
0
Order By: Relevance
“…Nbp35 and Cfd1 belong to the SIMIBI (signal recognition, MinD and BioD) (43) family of P-loop nucleoside triphosphatases (NTPases), forming a subgroup with several metal-binding and -trafficking proteins. The yeast Nbp35-Cfd1 complex possesses ATPase activity in vitro (18), and mutation of the Walker nucleotide-binding motifs impairs de novo [4Fe-4S] cluster assembly on this complex in vivo (13). Site-directed mutagenesis revealed cluster coordination via two essential cysteine ligands present in the conserved C-terminal CPxC motifs of both proteins.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Nbp35 and Cfd1 belong to the SIMIBI (signal recognition, MinD and BioD) (43) family of P-loop nucleoside triphosphatases (NTPases), forming a subgroup with several metal-binding and -trafficking proteins. The yeast Nbp35-Cfd1 complex possesses ATPase activity in vitro (18), and mutation of the Walker nucleotide-binding motifs impairs de novo [4Fe-4S] cluster assembly on this complex in vivo (13). Site-directed mutagenesis revealed cluster coordination via two essential cysteine ligands present in the conserved C-terminal CPxC motifs of both proteins.…”
Section: Significancementioning
confidence: 99%
“…Better mechanistic understanding of the eukaryotic CIA scaffold complex function will benefit from structural insights into the 3D architecture of these proteins, in particular the coordination of the transiently bound [4Fe-4S] cluster. We succeeded in crystallizing Cfd1 from the thermophilic fungus C. thermophilum (ct), which has a higher stability than Saccharomyces cerevisiae or human counterparts (13,18). The crystal structure [2.57-Å resolution; Protein Data Bank (PDB) ID code 6G2G] showed a ctCfd1 homodimer with a bound [4Fe-4S] cluster (Fig.…”
Section: Depletion Of Cfd1 Impairs Maturation Of Nuclear Fe-s Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saccharomyces cerevisiae it was identified as cytosolic Fe-S cluster deficient ( Cfd1 ) in a screen for genes able to convert Iron regulatory protein 1 into c-aconitase [20] [21]. These and subsequent studies in yeast and animal cell lines established that Nubp2 is an integral component of the cytosolic iron-Sulphur (Fe-S) cluster assembly (CIA) pathway where it acts along with its homologous binding partner Nubp1 as a scaffold for transfer of the Fe-S cofactor to non-mitochondrial apoproteins [2224]. Later studies revealed that knockdown of Nubp1 alone, or of both Nubp1 and Nubp2 , led to excessive centrosome duplication in vitro [25].…”
Section: Introductionmentioning
confidence: 99%
“…The bridging [4Fe‐4S] cluster is transiently assembled and can be transferred to apoproteins . The deviant Walker A motif is required for ATP binding and hydrolysis, and the ATPase activity is essential for in vivo Fe‐S cluster assembly and transfer .…”
mentioning
confidence: 99%